1991
DOI: 10.2307/1131134
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability and Resilience: A Study of High-Risk Adolescents

Abstract: Factors that allow children to maintain socially competent behaviors despite stress were examined among 144 inner-city ninth-grade students with a mean age of 15.3 years. Stress was operationalized by scores on a negative life events scale, and definitions of social competence were based on peer ratings, teacher ratings, and school grades. Moderator variables examined included intelligence, internal locus of control, social skills, ego development, and positive life events. Following theoretical models by Garm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
151
3
5

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 560 publications
(174 citation statements)
references
References 35 publications
12
151
3
5
Order By: Relevance
“…A 'resilient' subgroup is then defined as those who show little or no evidence of the negative outcome. Within this resilient group, the interaction of risk and protective factors is then examined, and inferences are made about how certain factors buffer others to serve a protective function (Luthar, 1991). However, defining resilience has been a very complex theoretical issue.…”
Section: Resiliency Researchmentioning
confidence: 99%
“…A 'resilient' subgroup is then defined as those who show little or no evidence of the negative outcome. Within this resilient group, the interaction of risk and protective factors is then examined, and inferences are made about how certain factors buffer others to serve a protective function (Luthar, 1991). However, defining resilience has been a very complex theoretical issue.…”
Section: Resiliency Researchmentioning
confidence: 99%
“…Locus of control is the personal characteristic that has shown the most consistent evidence of a stress-moderating effect in studies with children and young adults (Cauce, Hannan, & Sargeant, 1992;Luthar, 1991;Parkes, 1984). Theoretically, having an internal locus of control may serve a protective function by affecting appraisals of the stressful situation, coping efforts, or both.…”
mentioning
confidence: 99%
“…Therefore, while these adolescents demonstrated resilience in one area, other forms of   problems (i.e., depression) may have developed due to severe life stressors (Luthar, 1991).…”
Section: Background On Resiliencementioning
confidence: 99%
“…Neenan (2009) stated "no matter how robust you've become by dealing with tough times, you still remain vulnerable to coping poorly with future adversities" (p. 5). Likewise, one authority, Luthar (1991) demonstrated that adolescents in the midst of adversity who demonstrated high social competence, which is viewed as a resilient factor, may still have had difficulties in other areas of life. Specifically, the resilient adolescents from an innercity sample had significantly higher rates of depression and anxiety symptoms, compared to competent adolescents from backgrounds with lower stress levels.…”
Section: Background On Resiliencementioning
confidence: 99%